Rigid labour compensation and flexible employment? Firm-level evidence with regard to productivity for Belgium - Catherine Fuss; Ladislav Wintr (National Bank of Belgium, 2009)
Using firm-level data for Belgium over the period 1997-2005, we evaluate the elasticity of firms' labour and real average labour compensation to microeconomic total factor productivity (TFP). Our results may be summarised as follows. First, we find that the elasticity of average labour compensation to firm-level TFP is very low contrary to that of labour, consistent with real wage rigidity. Second, while the elasticity of average labour compensation to idiosyncratic firm-level TFP is close to zero, the elasticity with respect to aggregate sector-level TFP is high. We argue that average labour compensation adjustment mainly occur at the sector level through sectoral collective bargaining, which leaves little room for firm-level adjustment to firm-specific shocks. Third, we report evidence of a positive relationship between hours and idiosyncratic TFP, as well as aggregate TFP within the year
Keywords: J30; J60; 330; labour compensation; employment; hours; Total Factor Productivity; Lohnrigidität; Vergütungssystem; Arbeitszeit; Produktivität; Mikrofundierung; Belgien